Investigating the Bioactivity Potential and Standardization of Two Stingless Bee Propolis from East Kalimantan - Kustiawan, Paula Mariana; Syahbana, Muhammad Ali; Pratika, Rika; Ichsan, Muhammad Nor; Mentari, Ika Ayu; Hairunnisa, Indah; Setiawan, Irfan Muris; Syaifie, Putri Hawa; Ramadhan, Donny; Chanchao, Chanpen (Pharmaceutical Sciences and Research, 2024)
The standardization of raw materials from nature is essential before they are made into products. Until now, there is still limited information regarding the standardization of propolis from stingless bees. This research aims to determine the bioactivity with standardized specific and non-specific parameters of ethanol extracts from Homotrigona apicalis and Homotrigona fimbriata propolis. The methods include organoleptic tests, tests for water-soluble and ethanol-soluble compound content, drying shrinkage tests, specific gravity tests, water content tests, metal contamination tests, phytochemical screening, and determining total phenolic and flavonoid content. The free radical scavenging capacity was measured using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, and antimicrobial activity against Candida albicans, Propionibacterium acnes, Streptococcus mutans, Salmonella typhi, and Escherichia coli was assessed using the agar well diffusion method. The results indicated that the standardization parameters tested on H. apicalis and H. fimbriata propolis met the standard criteria. Both species contain alkaloids, flavonoids, phenolics, tannins, and saponins. Generally, the propolis extracts from these two stingless bees exhibit potential antioxidant and antimicrobial effects. The total phenolic content for H. apicalis was 0.963 ± 0.041 mg GAE/g, while for H. fimbriata, it was 0.345 ± 0.004 mg GAE/g. The total flavonoid content for H. apicalis was 12.066 ± 0.465 mg QE/g, and for H. fimbriata, it was 9.325 ± 0.031 mg QE/g. All these results can be used as a reference for developing products derived from stingless bees.